The value of diet therapy for the treatment of domestic cats which have hepatitis - Локес-Крупка, Т. П.; Канівець, Н. С.; Деренчук, Ю. І.; Крилевець, Ю. В. (Scientific Progress & Innovations, 2018)
Treatment of domestic cats for various types of liver pathology should be complex. In the occurrence of this illness a significant role is played by irregular and irrational feeding, which causes the metabolism of animals in general, so one of the important directions in the treatment of domestic cats with liver dysfunction is diet therapy. In our studies, we directed medical measures to eliminate the effect of this etiologic factor. In particular, the deficit of substances with a labile methyl group was offset, which is necessary to ensure the normal functioning of the liver. In addition, they ensured the receipt of irreplaceable (for cats) amino acids, the lack of which, in violation of the conditions of feeding, adversely affects, first of all, the function of the liver.